An emerging Panton–Valentine leukocidin-positive CC5-meticillin-resistant Staphylococcus aureus-IVc clone recovered from hospital and community settings over a 17-year period from 12 countries investigated by whole-genome sequencing. (February 2023) - Aloba, B.K.; Kinnevey, P.M.; Monecke, S.; Brennan, G.I.; O'Connell, B.; Blomfeldt, A.; McManus, B.A.; Schneider-Brachert, W.; Tkadlec, J.; Ehricht, R.; Senok, A.; Bartels, M.D.; et al.
Summary: Background: A novel Panton–Valentine leukocidin (PVL)-positive meticillin-resistant Staphylococcus aureus (MRSA) clonal complex (CC)5-MRSA-IVc ('Sri Lankan' clone) was recently described from Sri Lanka. Similar isolates caused a recent Irish hospital outbreak. Aim: To investigate the international dissemination and diversity of PVL-positive CC5-MRSA-IVc isolates from hospital and community settings using whole-genome sequencing (WGS). Methods: Core-genome single nucleotide polymorphism (cgSNP) analysis, core-genome multi-locus sequence typing (cgMLST) and microarray-based detection of antimicrobial-resistance and virulence genes were used to investigate PVL-positive CC5-MRSA-IVc ( N  = 214 including 46 'Sri Lankan' clone) from hospital and community settings in 12 countries over 17 years. Comparators included 29 PVL-positive and 23 PVL-negative CC5/ST5-MRSA-I/II/IVa/IVc/IVg/V. Results: Maximum-likelihood cgSNP analysis grouped 209/214 (97.7%) CC5-MRSA-IVc into Clade I; average of 110 cgSNPs between isolates. Clade III contained the five remaining CC5-MRSA-IVc; average of 92 cgSNPs between isolates. Clade II contained seven PVL-positive CC5-MRSA-IVa comparators, whereas the remaining 45 comparators formed an outlier group. Minimum-spanning cgMLST analysis revealed a comparably low average of 57 allelic differences between all CC5/ST5-MRSA-IVc. All 214 CC5/ST5-MRSA-IVc were identified as 'Sri Lankan' clone, predominantly spa type t002 (186/214) with low population diversity and harboured a similar range of virulence genes and variable antimicrobial-resistance genes. All 214 Sri Lankan clone isolates and Clade II comparators harboured a 9616-bp chromosomal PVL-encoding phage remnant, suggesting both arose from a PVL-positive meticillin-susceptible ancestor. Over half of Sri Lankan clone isolates were from infections (142/214), and where detailed metadata were available (168/214), most were community associated (85/168). Conclusions: Stable chromosomal retention of pvl may facilitate Sri-Lankan clone dissemination.